Identifying optimal approaches to implement colorectal cancer screening through participation in a learning laboratory. Issue 21 (25th October 2018) - Tangka, Florence K.L.; Subramanian, Sujha; DeGroff, Amy S.; Wong, Faye L.; Richardson, Lisa C.
Abstract : A total of 14 programs selected from among the 30 Centers for Disease Control and Prevention's Colorectal Cancer Control Program awardees are participating in the Colorectal Cancer Control Program learning laboratory to share information regarding the effectiveness and cost‐effectiveness of the interventions and lessons learned from the implementation processes. Herein, the authors present findings from the first set of 4 awardee programs in a series of 4 articles along with a methods article describing the data collection and analytic procedures used to perform comprehensive assessments